Southwest view of the Church of St. Helen - Schnebbelie, Robert Blemmell; Wise, William (Tufts Archival Research Center, 2008)
Bishopsgate Street, London. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.